Language and the Newborn Brain: Does Prenatal Language Experience Shape the Neonate Neural Response to Speech? - May, Lillian; Byers-Heinlein, Krista; Gervain, Judit; Werker, Janet F. (Frontiers in Psychology, 2011)
Previous research has shown that by the time of birth, the neonate brain responds specially to the native language when compared to acoustically similar non-language stimuli. In the current study, we use Near Infrared Spectroscopy to ask how prenatal language experience might shape the brain response to language in newborn infants. To do so, we examine the neural response of neonates when listening to familiar versus unfamiliar language, as well as to non-linguistic backwards language. Twenty monolingual English-exposed neonates aged 0-3 days were tested. Each infant heard low-pass filtered sentences of forward English (familiar language), forward Tagalog (unfamiliar language), and backwards English and Tagalog. During exposure, neural activation was measured across twelve channels on each hemisphere. Our results indicate a bilateral effect of language familiarity on neonates’ brain response to language. Differential brain activation was seen when neonates listened to forward Tagalog (unfamiliar language) as compared to other types of language stimuli. We interpret these results as evidence that the pre-natal experience with the native language gained in utero influences how the newborn brain responds to language across brain regions sensitive to speech processing.